The Ideology is Blowing in the Wind: Managing Orthodoxy and Popularity in China's Propaganda - Wang, Clyde Yicheng (Political communication, 2024)
The concept of political propaganda includes a theoretical contradiction between orthodoxy and popularity of ideology, and by implication, a practical contradiction between repressing and mobilizing public discourse. Post-socialist China offers a curious case. The neo-traditionalist bureaucratic system stresses absolute ideological correctness, while the mouthpiece media's need for adjusting to a marketized media industry demands popularity. How China confronts such contradiction is crucial for both understanding China's resilience and conceptualizing propaganda and ideology. Through in-depth interviews with insiders of the propaganda system, this article argues that China's mouthpiece media are compartmentalized into two separate branches. On one hand, the official print newspaper continues to define ideological orthodoxy. On the other, the newly developed online mouthpieces are granted greater autonomy to use various discursive strategies to popularize themselves. In the latter case, the subject of propaganda transforms from doctrine and dogma to discourse and culture, and ideology is integrated into everyday experience.